2022
DOI: 10.1007/s11071-022-07349-y
|View full text |Cite
|
Sign up to set email alerts
|

Based on robust sliding mode and linear active disturbance rejection control for attitude of quadrotor load UAV

Abstract: In this paper, a mass adaptive control method combining robust sliding mode control (SMC) and linear active disturbance rejection control (LADRC) is designed for the quadrotor load unmanned aerial vehicle (UAV) with mass variation. The scheme combines the advantages of SMC and LADRC. SMC can enhance the robustness of the controller, improve the anti-disturbance performance and overcome the problem of low control precision caused by bandwidth limitation of LADRC. The linear extended state observer (LESO) can es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…The simulation and experimental results showed that the control strategy could effectively improve the dynamic performance and stability of the speed control system. Wang et al [77] designed a quality adaptive control method, as shown in Figure 15, which combines robust sliding mode control (SMC) and linear active disturbance rejection control (LADRC). First, a mass-adaptive law was designed to remove the effects of mass variation.…”
Section: Active Disturbance Rejection Control Methodsmentioning
confidence: 99%
“…The simulation and experimental results showed that the control strategy could effectively improve the dynamic performance and stability of the speed control system. Wang et al [77] designed a quality adaptive control method, as shown in Figure 15, which combines robust sliding mode control (SMC) and linear active disturbance rejection control (LADRC). First, a mass-adaptive law was designed to remove the effects of mass variation.…”
Section: Active Disturbance Rejection Control Methodsmentioning
confidence: 99%
“…The combination of FTSO and FTDO is referred to as FTO. Different from previous observers that exhibit asymptotic convergence [16,26] or finite-time convergence [27,28,31,32], the proposed FTO can achieve fixed-time convergence of estimation errors, unaffected by initial errors. In addition, the FTO does not require strict assumptions on the system states which are difficult to satisfy as in [30,[36][37][38].…”
Section: Introductionmentioning
confidence: 91%
“…Питання керування безпілотними літальними апаратами часто розглядається дослідниками. Робіт і досліджень багато [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. У роботах автори розглядають методи основані на лінійні квадратичні регуляторах, пропорційно-інтегральних похідних, регуляторах з ковзним режимом та ін.…”
Section: вступunclassified